Aplikasi SPLDV dan Program Linier Dua Variabel dalam Menyelesaikan Permasalahan Kontekstual - Rama Dani, M Ardi; Octarina, Sisca; Puspita, Fitri Maya (Pendidikan Matematika FKIP Universitas Mataram, 2025)
This study aims to provide a concrete illustration of the application of systems of linear equations in two variables (SPLDV) and two-variable linear programming in solving real-world problems commonly encountered in daily life. The background of this research is rooted in the persistently low ability of students and small business practitioners to apply linear mathematical concepts to support decision-making processes, such as determining product prices and optimizing production. Using a descriptive method with a conceptual quantitative approach, this study presents two illustrative case studies: the determination of unit prices for stationery products through SPLDV, and the optimization of the production combination of woven bags and mats in a rattan-based small enterprise through two-variable linear programming under time constraints. The results indicate that SPLDV can objectively determine product prices based on transaction data, while linear programming provides an optimal solution in the form of producing 12 bags and 6 mats, yielding a maximum profit of IDR 1,320,000. These findings demonstrate that linear mathematical models serve as effective and applicable tools to support decision-making in both microeconomic contexts and mathematics education.